Performance evaluation of biocoagulant for the effective removal of turbidity and microbial pathogens from drinking water - Zenebe Nigussie; Nigus Gabbiye Habtu (IWA Publishing, 2023)
In this study, Moringa seeds, aloe vera leaves, and cactus leaves were used as biocoagulants for the treatment of drinking water. The effects of coagulant type, coagulant dosage, and pH were studied on the quality of the treated water. Response surface methodology was used to predict and optimize the parameters. The standard Six Jar test was used to measure the performance of coagulants. Three mixing modes were used in the jar test: quick mixing at 1 min at 120 rpm, slow mixing for 19 min at 40 rpm, and 15 min settling. The characterization results showed that extracts of Moringa seeds, aloe vera leaves, and cactus leaves contain 43.95 ± 0.49, 13.9 ± 0.42, and 10.94% ± 0.37 protein, respectively. It was revealed that coagulant type, coagulant dosage, and the interaction between (coagulant type (MS-SC and AV-SC) and pH) were significant (p < 0.05) for turbidity removal. Jar test results showed a removal efficiency of turbidity 98.83%, and 98.74% and 69.83% using MS-SC, and AV-SC and Ca-SC bio, respectively. These results imply that the three coagulants can be considered as effective, low-cost, and eco-friendly resources for the treatment of drinking water in rural communities of Ethiopia where access to clean water is scarce. HIGHLIGHTS Biocoagulants extracted from Moringa stenopetala seed, aloe vera leaves, and cactus leaves.; Salt is used as low-cost extractive agent in mild conditions.; Turbidity seems the main contributor to the deterioration of water quality.; Complete removal of E. coli was achieved.; Biocoagulants are inexpensive solutions for water treatment in rural areas.;